Aftereffect of single transcranial direct and alternating current stimulation on spontaneous home-cage and open-field EEG activities in a mouse model of Alzheimer’s disease - Sun, Huaying; Wang, Yumei; Yuan, Dong; Duan, Mengsi; Chen, Zhuangfei; Fu, Yu (Frontiers in Aging Neuroscience, 2024)
BackgroundAs a non drug and non invasive therapy, both transcranial alternating current stimulation (tACS) and transcranial direct current stimulation (tDCS) may modulate cortical rhythms and serve as potentially effective approaches to cognitive decline in Alzheimer’s disease (AD). However, studies using animal models of AD are quite limited.MethodsThis study investigates the aftereffects of tACS and tDCS on brain EEG activity and associated exploratory behavior in normal aged and APP/PS1 transgenic mice (15 months old). Anodal tDCS and 10 Hz tACS (350 μA, 20 min) were applied once and EEGs were recorded from the hippocampus (Hip) and prefrontal cortex (PFC) during spontaneous home-cage state and open-field exploration.ResultsA key finding was that tDCS induced significant alpha (8–12 Hz) EEG changes while tACS induced peak frequency changes in the group difference between normal aged and AD mice. However, both groups showed similar increases in theta (4–8 Hz) EEG activity during open-field exploration and increases in gamma (20–100 Hz) EEG activity in spontaneous state, suggesting that the ongoing physiological state may be related to some of the EEG changes.ConclusionThis study provides insight into the short-term aftereffects of transcranial current stimulation in the aging and AD brain and is the first animal study to compare brain activity between tACS and tDCS treatments.